2016
DOI: 10.1098/rspb.2016.1986
|View full text |Cite
|
Sign up to set email alerts
|

Attention-like processes in insects

Abstract: Attention is fundamentally important for sensory systems to focus on behaviourally relevant stimuli. It has therefore been an important field of study in human psychology and neuroscience. Primates, however, are not the only animals that might benefit from attention-like processes. Other animals, including insects, also have to use their senses and select one among many stimuli to forage, avoid predators and find mates. They have evolved different mechanisms to reduce the information processed by their brains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 92 publications
(159 reference statements)
1
44
0
Order By: Relevance
“…13,18 We argue that findings do not need to be weighted by phylogenetic distance from humans, and many examples of animal turn-taking 9,19,21,24 are still interesting in their own merit without advocating cooperation or social cognition. "Lower level" processes, such as attention, 30 signal masking, 35,77 and fixed time lags 31 may suffice to explain much of animal turn-taking behavior. In particular, animal chorusing, as long as this is not defined as "a cacophony of sounds," 13 may provide a broader biological foundation for turn-taking without assuming intentionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,18 We argue that findings do not need to be weighted by phylogenetic distance from humans, and many examples of animal turn-taking 9,19,21,24 are still interesting in their own merit without advocating cooperation or social cognition. "Lower level" processes, such as attention, 30 signal masking, 35,77 and fixed time lags 31 may suffice to explain much of animal turn-taking behavior. In particular, animal chorusing, as long as this is not defined as "a cacophony of sounds," 13 may provide a broader biological foundation for turn-taking without assuming intentionality.…”
Section: Discussionmentioning
confidence: 99%
“…40,74,90 This mapping is complex, nonlinear, and a potential subject for exciting future research. It must include at least four explanatory levels, illustrating (1) how neural processes occur within an individual nervous system (e.g., oscillations, predictive coding, and climbing neural activity [94][95][96][97][98] ); (2) possibly supporting different cognitive mechanisms; 13,14,30,40,60,74 (3) which result in a range of individual timing patterns that can be measured behaviorally; 12,37,45,46,49 and that (4) shape and are shaped by interindividual interaction. 14,39,71,98…”
Section: Turn-taking Does Not Imply Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in several insects have revealed attention-like processes involved in selection of one among many visual and auditory stimuli (van Swindern and Greenspan, 2003; Spaethe et al ., 2006; Wiederman and O’ Carroll, 2013; de Bivort and van Swindern, 2016), and careful comparisons of the mechanistic similarities between insects and primates have been carried out (cf. Nityananda, 2016). Very little work, however, has been published on olfactory attention.…”
Section: [Discussion]mentioning
confidence: 99%
“…When there is more than one target, predatory insects must decide on which one to orient towards (e.g. Rossel, 1996;Wiederman & O'Carroll, 2013;Nityananda, 2016). They must also avoid inedible or toxic prey (e.g.…”
Section: Introductionmentioning
confidence: 99%